Utilization of Artificial Intelligence in Personalized Learning - Nindia, Astrid; Firdausi, Mirma Yudha; Prapantja, Yudha; Zulfitria, Zulfitria (Journal of English Language and Education, 2026)
The rapid advancement of artificial intelligence (AI) over the past decade has driven significant transformations in educational practices, particularly through the implementation of personalized learning. This article aims to comprehensively examine the utilization of AI in supporting adaptive, learner-centered personalized learning and to identify the opportunities and challenges associated with its implementation. This study adopts a literature review approach by analyzing relevant peer-reviewed journal articles retrieved from Google Scholar published between 2015 and 2025. The findings indicate that the application of Intelligent Tutoring Systems, Adaptive Learning Management Systems, and Generative AI enables the dynamic adaptation of learning content, pacing, and learning pathways based on individual learner profiles, thereby enhancing learner engagement, learning efficiency, and academic achievement. Furthermore, the role of educators is shifting from content delivery toward facilitation and mentoring of the learning process. Nevertheless, the integration of AI in education also presents critical challenges, including data privacy concerns, algorithmic bias, AI hallucinations, and the risk of depersonalization in learning environments. This article underscores the importance of adopting a human-centered and ethical approach to AI integration to ensure that personalized learning is implemented effectively, equitably, and sustainably.